Ragam Budaya Penggunaan Piranti Sumpit Masyarakat Bandung - Selvia, Selvia (Paradigma: Jurnal Kajian Budaya, 2021)
Food is an inseparable part of a culture and serves as one of the characteristic markers of a culture or ethnic groups. The arrival and presence of the Chinese ethnic group has contributed to the diversity of the Indonesian culture in general. One of Chinese dishes that have become a favorite delicacy in Bandung is noodles, a wide variety of which is sold in various areas around the city. Noodles are considered as a substitute for daily staple food and have become part of Indonesian identity in general. This field study used the descriptive qualitative method. Data collection was carried out through interviews and observations using the purposive sampling method. The purpose of this study is to determine the various ways Bandung people use chopsticks when consuming noodle. Results show that most Bandung people consumed noodles using spoons and forks. Their lack of understanding of the philosophy of noodles and chopsticks results in an inappropriate noodle-eating etiquette.